2010
DOI: 10.1016/j.funbio.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

AFLP analysis reveals a clonal population of Phytophthora pinifolia in Chile

Abstract: Phytophthora pinifolia is the causal agent of the recently discovered needle disease of Pinus radiata in Chile, referred to as "Daño Foliar del Pino" (DFP). The genetic structure of the pathogen population is unknown, which hinders our understanding of its appearance and spread in Chile since 2004. In this study, a population of 88 cultures of P. pinifolia isolated from P. radiata at several localities in Chile was evaluated for genotypic diversity using amplified fragment length polymorphisms (AFLPs). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…This is in contrast to many other Phytophthora spp., such as P. ramorum that has a wide range of hosts Rizzo et al 2005;Tooley and Browning 2009). The fact that P. pinifolia has been found only in Chile and its low genetic diversity (Durán et al 2010) suggests strongly that it is a pathogen specific to Pinus spp.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to many other Phytophthora spp., such as P. ramorum that has a wide range of hosts Rizzo et al 2005;Tooley and Browning 2009). The fact that P. pinifolia has been found only in Chile and its low genetic diversity (Durán et al 2010) suggests strongly that it is a pathogen specific to Pinus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, a serious foliage disease of Pinus radiata caused by an undescribed species of Phytophthora, P. pinifolia, was reported in Chile (Durán et al 2008). Low levels of genetic diversity within the population of this oomycete indicated that it was a recent introduction to the country (Durán et al 2010). Its origin remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In present times, a species like Phytophthora sojae is hampering soybean production in several continents (Kamoun 2001). Other plant pathogens, such as Phytophthora cinnamomi, P. pinifolia and P. ramorum are causing major damages to forest ecosystems and to the wood industry in Australia, Chile and the USA (Duran et al 2010;Rizzo et al 2005). In addition, several species are pathogenic to animals, such as Saprolegnia parasitica, which has a major impact on salmon farming (Phillips et al 2008), Pythium insidiosum, a human pathogen (Mendoza and Newton 2005) or Leptolegnia chapmani, a parasite of mosquito larvae (Zattau and McInnis 1987).…”
Section: Introductionmentioning
confidence: 99%